RESISTANCE TRAINING FOR YOUTH ATHLETE DEVELOPMENT - Sanpasitt, Chanawat (Academic Journal of Thailand National Sports University, 2022)
Enhancing muscle performance for young athletes by resistance training is an important process to long-term athlete development. It is aims to improve muscle strength which is a key component of biomotor ability. Resistance training can be performed via using various types of equipment such as body weights, weight machines, or free weights. However, it is a critical time of rapid physical and emotional changes with a distinguished development of human structures and systems during puberty and adolescence. Therefore, proper physical and mental preparation are major factors that young athletes should be considered. An appropriate program designed and supervised resistance training programs is relatively safe for youth. Numerous instructions for youth resistance training programs should include the correct lifting technique, training volume, safety training, spotting techniques, and how to use different types of equipment regarding to growth development. Resistance training can improve muscle strength, increase bone mineral density, and reduce the risk of fractures and injuries during training and competition. Coach should understand clearly in the training process according to the long-term athlete development that related to maturity and growth. The potential and adequate resistance training for youth approach to a higher-level athlete with good performance and effective movement.